Demonetization and Its Effects on BSE SENSEX and Some Sectoral Indices: An Exploratory Econometric Analysis - Debabrata Mukhopadhyay; Nityananda Sarkar (International Econometric Review (IER), 2019)
This study has carried out some preliminary time series analyses to examine the impacts of demonetization which was carried out in India on 8 November 2016, on the well-known Indian stock index, BSE SENSEX, and four major sectoral indices viz., BSE BANKEX, BSE Auto, BSE Reality and BSE Smallcap, using daily level time series data covering the period 1 January 2016 to 31 May 2017. Apart from examining the stationarity/ nonstationarity property and existence of structural breaks after demonetization in these series, the paper has also studied the trend behavior and returns models for both the pre- and post-demonetization periods. This study has found that while there is more than one break in all the five series at their level values, there is only one structural break after demonetization. It has been found that the trend function for all the index series broadly gives support to this finding of one break after demonetization. Further, some changes have been observed in the stationary models for the two sub-periods of pre- and postdemonetization for all but BSE Auto index. Finally, except for BSE SENSEX, no change in the status of stationarity/nonstationarity in the pre- and post- demonetization periods has been found in the other series.
Keywords: C22; G18; G28; 330; Bai-Perron Multiple Break Points Test; Demonetization; Stationarity; Structural Breaks; Sup MZ Test